2008
DOI: 10.4049/jimmunol.181.3.2010
|View full text |Cite
|
Sign up to set email alerts
|

Selection of the Alternative Exon 1 from thecd5Gene Down-Regulates Membrane Level of the Protein in B Lymphocytes

Abstract: The human cd5 gene has two alternative exons 1: exon 1A (E1A) which encodes the full-length (FL) CD5 protein and exon 1B (E1B) which encodes a truncated (TR) isoform. The FL variant of CD5 protein is translocated to the plasma membrane, while its TR variant is retained in the cytoplasm. Because there is an inverse relationship between the levels of FL-CD5 and TR-CD5 in B cells, we have addressed the issue of how the selection of exon 1 is determined. In leukemic B cells, DNA methyltransferase (DNMT)1-induced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…Results generated from our previous studies indicated that the modulatory effects of CD5 protein on BCR signaling are attributed to the CD5 isoform which contains E1A, the previously documented exon 1. Introduction of cDNA for the recently identified CD5-E1B isoform into CD5 ϩ T and B cells reduced membrane expression of CD5 protein (17,19). Coexpression experiments have also shown that in the presence of CD5-E1B, CD5-E1A was not translocated to the membrane but associated with CD5-E1B in cytoplasmic aggregates (19).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Results generated from our previous studies indicated that the modulatory effects of CD5 protein on BCR signaling are attributed to the CD5 isoform which contains E1A, the previously documented exon 1. Introduction of cDNA for the recently identified CD5-E1B isoform into CD5 ϩ T and B cells reduced membrane expression of CD5 protein (17,19). Coexpression experiments have also shown that in the presence of CD5-E1B, CD5-E1A was not translocated to the membrane but associated with CD5-E1B in cytoplasmic aggregates (19).…”
Section: Discussionmentioning
confidence: 97%
“…Introduction of cDNA for the recently identified CD5-E1B isoform into CD5 ϩ T and B cells reduced membrane expression of CD5 protein (17,19). Coexpression experiments have also shown that in the presence of CD5-E1B, CD5-E1A was not translocated to the membrane but associated with CD5-E1B in cytoplasmic aggregates (19). The exact dynamics of the interaction between CD5-E1B and CD5-E1A remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations